Flaubert et Hugo : d’une esthétique à l’autre - Takashi Kinouchi (Flaubert: Revue Critique et Génétique)
Hugo played an important role in Flaubert’s literary evolution. He exerted a major influence on Flaubert’s creation. But Flaubert also tried to distance himself from the Romantics’ leader. This article studies how Flaubert built his aesthetic theory with and against Hugo’s. We will confront Flaubert’s letters with Hugo’s critical writings, in particular the Preface to Cromwell.